The choice and use of digital teaching material by higher education teachers: the evolution of TDIC in the virtual learning environment (Research, Society and Development, 2023)
The various existing means of communication and information technologies stimulated by the internet make it possible to think about how to use them in teaching and learning processes. The objective of this article is to analyze the types of files used in virtual learning environments and the evolution of the use of technological tools and digital teaching materials, identifying the pandemic period of Covid-19 as a possible accelerator of this process. The collection of data from Moodle, with the extension of the archives of higher education courses at the Federal University of Santa Maria, present answers about how digital didactic materials were used as mediators of interactions between professors and students in the teaching and learning process, requiring continuity of studies on this subject, prolonging what we like to identify, and what could advance so that the mediation takes place efficiently, aiming at complementing the teaching process and the learning process with the integration between teacher and student in the environments virtual.